2021
DOI: 10.1038/s41467-021-25701-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2, proof of concept, randomised controlled trial of berberine ursodeoxycholate in patients with presumed non-alcoholic steatohepatitis and type 2 diabetes

Abstract: Non-alcoholic steatohepatitis is frequently associated with diabetes and may cause progressive liver disease. Current treatment options are limited. Here we report on a prospective, randomised, double-blind, placebo-controlled trial of two doses of HTD1801 (berberine ursodeoxycholate, an ionic salt of berberine and ursodeoxycholic acid), versus placebo that was conducted in 100 subjects with fatty liver disease and diabetes (NCT03656744). Treatment was for 18 weeks with a primary endpoint of reduction in liver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 36 publications
0
19
0
4
Order By: Relevance
“…It is an isoquinoline quaternary alkaloid distributed in the roots, rhizomes, stems, and bark of several botanicals or herbs like Coptis chinensis (Chinese goldthread), Coptis rhizome , Berberis vulgaris , Argemone mexicana , etc., In aging research, berberine has been shown to extend the lives of several laboratory-adapted species. Regarding aging-related diseases, berberine is known to exert numerous beneficial outcomes in individuals with diabetes type II because of its profound effects on alleviating endothelial dysfunction and lipid metabolic imbalance and improving glycemic control, insulin sensitivity, and insulin secretion via targeting KCNH6 potassium channels ( Zhang et al, 2008 ; Harrison et al, 2021 ; Zhao et al, 2021 ). Aside from diabetes type II, berberine has been demonstrated to have neuroprotective effects on aging-cognitive disorders and is also considered a potent chemosensitizer and chemoprotector for numerous cancers ( Shang et al, 2020 ; Devarajan et al, 2021 ).…”
Section: Clinical Utility and Control Of Biological Aging And Age-rel...mentioning
confidence: 99%
“…It is an isoquinoline quaternary alkaloid distributed in the roots, rhizomes, stems, and bark of several botanicals or herbs like Coptis chinensis (Chinese goldthread), Coptis rhizome , Berberis vulgaris , Argemone mexicana , etc., In aging research, berberine has been shown to extend the lives of several laboratory-adapted species. Regarding aging-related diseases, berberine is known to exert numerous beneficial outcomes in individuals with diabetes type II because of its profound effects on alleviating endothelial dysfunction and lipid metabolic imbalance and improving glycemic control, insulin sensitivity, and insulin secretion via targeting KCNH6 potassium channels ( Zhang et al, 2008 ; Harrison et al, 2021 ; Zhao et al, 2021 ). Aside from diabetes type II, berberine has been demonstrated to have neuroprotective effects on aging-cognitive disorders and is also considered a potent chemosensitizer and chemoprotector for numerous cancers ( Shang et al, 2020 ; Devarajan et al, 2021 ).…”
Section: Clinical Utility and Control Of Biological Aging And Age-rel...mentioning
confidence: 99%
“…UDCA, in turn, is a bile acid long used for the treatment of NASH and chronic cholestatic diseases, whose hepatoprotective effects are confirmed by several systematic reviews and meta-analyses [ 200 , 201 ]. In a phase 2 proof-of-concept RCT in T2DM patients with presumed NASH, BUDCA reduced liver enzyme levels and liver steatosis by MRI-PDFF [ 202 ].…”
Section: Other Agentsmentioning
confidence: 99%
“…Sixthly, recently, clinical research on BBR has increased, primarily focusing on metabolic diseases, such as nonalcoholic liver disease, diabetes, and hyperlipidemia ( Li et al, 2019a ; Zhang et al, 2020c ; Di Bisceglie et al, 2020 ; Zhao et al, 2021b ; Harrison et al, 2021 ), and digestive system diseases, such as ulcerative colitis ( Xu et al, 2020 ) and colorectal adenoma ( Chen et al, 2020 ). BBR ursodeoxycholate and BBR chloride are involved in this process.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%